2005
DOI: 10.1159/000089222
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Treatments for Electromagnetic Hypersensitivity

Abstract: Background: Electromagnetic hypersensitivity (EHS) is a poorly understood condition in which patients report symptoms following perceived exposure to weak electromagnetic fields (EMFs) such as those produced by mobile phones or visual display units. Little is known about the aetiology of the condition although experimental data suggest that EMFs are an unlikely causal agent. In this systematic review we assessed the efficacy of any treatment for people reporting EHS. Methods: Twelve literature databases were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 25 publications
(35 reference statements)
2
42
0
Order By: Relevance
“…Whereas the existence of subjective pathways is beyond controversy, there is scientifi c uncertainty whether exposure levels to which the general population is typically exposed can cause adverse health effects through a biological mechanism. A systematic review of blind and double-blind provocation studies comparing the perception of EMFs of EHS and Non-EHS individuals did not fi nd evidence that EMF below standard limits can be perceived in a blind setting (Rubin et al 2005). The authors stated that it was diffi cult to prove that EMF exposure could trigger these symptoms and came to the conclusion that EHS was probably unrelated to the presence of EMF.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the existence of subjective pathways is beyond controversy, there is scientifi c uncertainty whether exposure levels to which the general population is typically exposed can cause adverse health effects through a biological mechanism. A systematic review of blind and double-blind provocation studies comparing the perception of EMFs of EHS and Non-EHS individuals did not fi nd evidence that EMF below standard limits can be perceived in a blind setting (Rubin et al 2005). The authors stated that it was diffi cult to prove that EMF exposure could trigger these symptoms and came to the conclusion that EHS was probably unrelated to the presence of EMF.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have typically demonstrated that sham exposure is as likely to trigger symptoms as genuine exposure to electromagnetic fields. This has led some authors to suggest that psychological factors may play an important role in causing or perpetuating the condition [Rubin et al, 2008;Stovner et al, 2008] and that sufferers may therefore respond better to treatments based on cognitive behavior therapy than to interventions involving avoidance of electrical equipment or reduction of exposure [Rubin et al, 2006]. It is possible, however, that exposure to electromagnetic fields might trigger biological effects that may lead to the experience of symptoms in people with IEI-EMF that are too subtle to detect using selfreported measures, but which might be observable by studying physiological changes.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is described as electromagnetic hypersensitivity or "idiopathic environmental intolerance with attribution to electromagnetic fields." [5][6][7][8] Additionally, individuals who are hypersensitive to electromagnetic fields often claim to be able to perceive radiofrequency electromagnetic fields in their daily life. 6 People are generally exposed to MPBS radiation under far-field conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%